Comparision of the effects of the central posteroanterior mobbilization to the thoracic rotary posteroanterior manipulation in the treatment of bilateral mechanical neck pain - Manida Kongsawatvarakul (Chulalongkorn University, 2012)
Thesis (M.Sc.)--Chulalongkorn University, 2008